Estresse em cordeiros pelo transporte rodoviário e seu efeito sobre características da carcaça e carne - Fredson Vieira e Silva (2014)
The transport of lambs, when in an inappropriate way, cause problems in the animals welfare and losses on carcass and meat traits. In this context, we aimed to evaluate lambs during and after road transport, and their carcasses and meat subjected to different areas occupied by animals and driven transport times. We used eighty lambs distributed into a randomized design in a 4 x 4 factorial scheme, four groups with different occupied areas ( 0.180, 0.208, 0.235 and 0.277 m2 animal-1 of 36,64±2,13 kg) during each journey and four different trips with increasing driven times (105, 232, 452 and 630 min). This work was divided into four sections, in the first one it is discussed on the behavior of lambs during transportation, after that on physiological and hematological changes, and finally, loss of body weight and carcass and meat quality characteristics. Lambs transported in the group 0.180 m2 animal-1 had lower chances to lie, in the group 0.208 m2 animal-1, when they laid, they had difficulty in getting up. These results led to two cases of severe bruises on carcasses. The enlargement of space during the trip did not increase the number of injuries, or loss of balance and falls. The concentrations of adrenaline increased with the duration of the journey and they were softened with the enlargement of space. Same behavior was observed for loss of body weight. The equation = 426.5976 + 8.4825 time - 0.0371 (area x time2) can be used to determine these losses in grams. The cortisol and creatine kinase showed higher concentrations for longer journeys in the pre slaughter. The enlargement of space during the transportation did not affect carcass traits. Longer transportations significantly increased losses in hot and cold carcass: they were found increases in losses about 0.28 and 0.30 kg for every driven 100 km, respectively. Weight losses of meat during thawing were increasing with longer journeys and also in lambs that were allocated in larger spaces, even with no difference in the ultimate pH. Lambs in longer transportation had meat with the larger losses during cooking and larger shear forces. The longer transportation the more decreased the meat red content.